Identification of historical plant material using micro-computed tomography. (July 2013) - Smith, Catherine; Lowe, Bronwyn; Blair, Kate; Carr, Debra; McNaughton, Andrew
Abstract : This work investigates the use of micro-computed tomography (micro-CT) for identification of New Zealand plant leaf material from artefacts. Micro-CT was explored as a result of difficulties in preparing transverse sections from aged plant material artefacts to compare with reference slides for microscopic identification of plant species. Plant names in te reo Māori (Māori language) are followed by the English name and botanic name, and are subsequently referred to by Māori names. The three plants investigated (harakeke, New Zealand flax, Phormium tenax, J. R. Forst & G. Forst; tī kōuka, cabbage tree, Cordyline australis, (Forst.f.) Endl, ; kiekie, Frecinetia banksii A.Cunn.) were/are commonly used by Māori for the manufacture of objects often found in cultural institutions. Contemporary and historical specimens (from artefacts) of plant leaf material were investigated. Contemporary specimens were viewed using micro-CT and showed identifiable features compared with micrographs of transverse sections from reference material. Diagnostic features of each plant species were then named and measured, providing the basis for development of an identification key using both visual and objective criteria. Positive identification of historical specimens using this key varied across plant species and according to level of ageing and processing. Despite this, micro-CT had several advantages over traditional transverse sections: samples were not prepared for, or altered by, analysis, and numerous cross sections across the entire sample could be easily viewed to locate identifiable characteristics. Although measurable criteria supplied apply only to the three named New Zealand plant species, this paper provides methods that could be applied to the identification of other aged plant leaf material. Knowledge of plant anatomy at the level of major cell and tissue types (e.g. mesophyll, sclerenchyma, vascular tissue, and epidermis) is sufficient for the level of analysis carried out in this study.